2020
DOI: 10.1002/cam4.3290
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical related donor vs matched sibling donor allogeneic hematopoietic stem cell transplantation for acute myeloid leukemia and myelodysplastic syndrome aged over 50 years: A single‐center retrospective study

Abstract: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is a potentially curative therapeutic option for patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS). Increasing data suggest that haploidentical donor (HID) transplantation achieve comparable outcomes with HLA‐matched sibling donor (MSD) in adult AML/MDS. This retrospective study compared the outcomes of AML or MDS patients age ≥50 years underwent HID and MSD transplantation. One hundred and fifty‐six patients were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…Consistently, several centers in China obtained similar results for SAA patients (13)(14)(15). The haploSCT cohorts with AML, MDS, or Ph+ ALL, including haplo-cord-HSCT, had higher CMV viremia than the HLA-matched HSCT cohorts (16)(17)(18)(19), but the incidence of CMV disease was not significantly different between the two groups. Even in pediatric patients with MDS or patients with relapsed/ refractory acute lymphoblastic leukemia after CAR-T therapy who underwent haploSCT, the incidence of CMV reactivation/ infection was less than 60%, and very few patients developed CMV disease (20,21).…”
Section: Incidence Of Cytomegalovirus Infection After Haplosctsupporting
confidence: 65%
“…Consistently, several centers in China obtained similar results for SAA patients (13)(14)(15). The haploSCT cohorts with AML, MDS, or Ph+ ALL, including haplo-cord-HSCT, had higher CMV viremia than the HLA-matched HSCT cohorts (16)(17)(18)(19), but the incidence of CMV disease was not significantly different between the two groups. Even in pediatric patients with MDS or patients with relapsed/ refractory acute lymphoblastic leukemia after CAR-T therapy who underwent haploSCT, the incidence of CMV reactivation/ infection was less than 60%, and very few patients developed CMV disease (20,21).…”
Section: Incidence Of Cytomegalovirus Infection After Haplosctsupporting
confidence: 65%
“…It has been shown that the incidence of infection after HID HSCT is higher than HLA-matched transplantation due to the delayed immunologic reconstitution 23,24 . It is especially apparent in HID transplantation with ATG-based regimens 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A fresh analysis conducted by the Chronic Malignancies Working Party of European Society for Blood and Marrow Transplantation suggested that the MSD remains the preferred choice over the HID in myelodysplastic syndromes, despite the baseline older donor age of 55 years in MSD than 36 years in HID [ 19 ]. A single-center study with significant inequivalent donor age showed similar outcomes achieved in HID and MSD groups [ 20 ]. Large variations of outcomes from several studies can be brought on because of baseline imbalances.…”
Section: Discussionmentioning
confidence: 99%